Isolation and sequence analysis of p53 cDNA from human prostate tissue - Nur Diana, Anuar. (Universiti Malaysia Sarawak (UNIMAS), 2005)
p53 is one ofthe tumor suppressor gene and can be translated from a single mRNA with a single open reading frame. It comprises 393 amino acids residues and includes three main functional domains; an N-terminal transactivation domain (TAD), a central DNA binding core domain (DBD) and a C-tenninal oligomerization domain (OLD). Mutations in the p53 gene on chromosome 17p appear to be the most common genetic change in cancers. The p53 gene has been coined the 'guardian of the genome' as it prevents the progression through the cell cycle. allowing DNA damaged through normal 'wear and tear' to be repaired which provides evidence for a single 'hit' model for the inactivation of normal p53 as an acquired event in predisposition to cancers. The present study was focused on the isolation ofp53 cDNA from human prostate total RNA using Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) and DNA sequencing strategies. p53 cDNA was isolated from both normal human prostate and prostate adenocarcinoma total RNA by using an established set of primers. The desired length of gene were successfully cloned into pGEM""-T Vector System and sent to 1 sl Base Laboratories for sequencing. However, the sequences data obtained were too ambiguous and did not provide good result for nucleotide comparison. Hence, no mutational analysis accomplished for prostate adenocarcinoma.